Lectinas purificadas de sementes de Parkia nitida MIQ. e Parkia panurensis EX H. C. Hopkins: determinação da estrutura primária e atividade citotóxica contra náuplios de Artemia - Bari, Alfa Umaro (2021)
Lectins are proteins found in all classes of living organisms. They perform several biological functions, and in plants they present as one of the functions the defense against pathogens and predators. The biological functions of lectins are related to their ability to recognize and bind reversibly to carbohydrates. Two new lectins from Parkia panurensis and Parkia nítida seeds (family Leguminosae; subfamily Mimosoideae) were successfully purified in this work through the combination of protein chemistry techniques, such as ammonium sulfate precipitation and affinity, ion exchange and molecular exclusion chromatographies. The new lectins, called PpaL and PNL, are non-glycosylated metalloproteins and specific for the sugars D-mannose, D-glucose and their derivatives. They are also stable over a wide temperature and pH range. The PpaL had an intact molecular mass of 50.5660 Da, whereas PNL has an intact molecular mass of 48760.3008 Da. Both lectins in solution in the native condition behave like a dimer. The partial sequencing of the primary structure of the PpaL resulted in a total of 334 amino acid residues corresponding to 75% of the total coverage, while the primary structure sequence of NLP resulted in a total of 451 amino acid residues corresponding to the total coverage of the sequence. Both PpaL and PNL showed high homology with other lectins of the genus Parkia. Structural studies of PNL suggest possible post-translational processing for lectins of the genus Parkia. PpaL and PNL are toxic against Artemia sp with an LC50 value of 20 and 61.38 µg/mL respectively. Several biological activities of lectins of the genus Parkia have been reported. These characteristics make them good alternatives as biopharmaceuticals and candidates for the treatment of different types of diseases.